ANALISIS MAKNA DENOTASI DAN KONOTASI PADA PENAMAAN BRAND MAKANAN DI KOTA MALANG - Baedt Giri Mukhoddam Billah Giri; Abdul Muntaqim Al Anshory Al Anshory; Agwin Degaf Degaf (PRASI, 2023)
The purpose of this research is to map the naming of food brands that have both denotative and connotative meanings for food merchants in Malang City. This study employed a qualitative descriptive method with a semantic approach to examine terms in food brands. The object of this study is the  naming of food brands in Malang City, East Java, Indonesia. Observation and interviews were used as data gathering methods. The data collected for each term in Malang City's food brands were analyzed for denotation and connotation meaning aspects. The results of the study show that food brands in Malang City use terms with denotative and connotative meanings. The brand's connotative meaning differs greatly from its denotative meaning. According to the findings of this study, the names of their food brands are chosen using four approaches: 1) adapting the concept of a currently viral food brand, 2) being representative, 3) adapting buyer remarks, and 4) thinking about names as sales progress. Keywords : Culture, identity, connotative meaning, denotative meaning, brand.   Abstrak Penelitian ini bertujuan untuk memetakan penamaan brand makanan yang mengandung makna denotasi dan konotasi pada pedagang makanan di Kota Malang. Penelitian menggunakan metode deskriptif kualitatif dengan pendekatan semantik yang berfungsi menganalisis kata dalam brand makanan. Objek penelitian ini adalah penamaan brand makanan di Kota Malang, Jawa Timur Indonesia. Teknik pengumpulan data dilakukan dengan pengamatan dan wawancara. Data yang diperoleh pada setiap kata dalam brand makanan di Kota Malang dianalisis unsur makna denotasi dan konotasi. Hasil temuan dari penelitian ini menunjukkan bahwa brand makanan di Kota Malang menggunakan kata yang berimplikasi pada makna denotasi dan konotasi. Dan makna konotasi pada brand tersebut jauh berbeda dari makna denotasinya. Penelitian ini menyimpulkan bahwa pengambilan nama pada brand makanan mereka melalui empat pendekatan yang berupa 1) adaptasi konsep brand makanan yang sedang viral, 2) representatif, 3) adaptasi komentar pembeli, dan 4) memikirkan nama seiring berjalannya penjualan.